Maintenance Activity Planning by Reability Centered Maintenance II Method - Hidayat, Rachmad; Ansori, Nachnul; Imron, Ali (Makara Journal of Technology, 2010)
Maintenance Activity Planning by Reability Centered Maintenance II Method. This research discusses maintenance activity planning using the RCM II method to evaluate failure function risk on compresor screw. The calculation of maintenance time is performed by considering maintenance and repair costs. The risk evaluation result with RPN shows that the critical component that needs to get the main priority in applying maintenance on compresor screw is function disorder on timeworn piston and on the broken outgoing air sponge’s filter that receives RPN 45. The optimum maintenance time calculation is applied on components that undergo scheduled restoration and scheduled discard task so that this action becomes technically feasible in decreasing the consequence of damage. The optimum maintenance time value that is acquired to prevent damage on compresor screw is lower than the value of its MTTF, which demonstrates that optimum maintenance time will be significant in avoiding component function damage before the damage happens.